AN INVESTIGATION OF EFFECT OF PROBLEM-SOLVING SKILL ON JOB SATISFACTION OF PROVINCIAL FOOTBALL REFEREES IN EASTERN ANATOLIAN REGION - Kızılkoca, Mustafa; Özcan, Ecesu; Albayrak, Veysel (My University, 2020)
The aim of this study is to present an effective study on the regional basis that examines the effect of the problem solving skills of the provincial football referees on the level job satisfaction and to contribute to the literature of sports science. The collected data were analyzed with SPSS 25.0 package program and frequency analysis, factor analysis, t test, ANOVA and regression analysis were applied to the data set which parametric tests were used to analyze. From the findings of the analysis, it was concluded that problem solving skill negatively affects job satisfaction, and in response to other sub-problems, the referees with 5-10 years of professional experience have the highest level of problem solving skills and when compared to men, the average score of problem solving skill and jobs satisfaction of women are higher. Finally, regarding the fact that the problem solving skill is higher in the period of 1-5 years, with respect to years in occupation, it has been thought that the new hired individuals are idealistic due to the competitive factor and economic expectations. The result of the study is that problem solving ability has a negative effect on job satisfaction, which constitutes the problem statement of our research. The fact that the demographic distribution is very high in the new generation (22-29 years old) has given us specific results regarding the need for current research with the work discipline, work perspective, emotional state, economic expectations of the individuals of this new generation.
Keywords: Spor Bilimleri